Evaluation of silica-nanotubes and strontium hydroxyapatite nanorods as appropriate nanoadditives for poly(butylene succinate) biodegradable polyester for biomedical applications - Grigoriadou, I.; Nianias, N.; Hoppe, Alexander; Terzopoulou, Z.; Bikiaris, D.; Will, Julia; Hum, Jasmin; Roether, Judith; Detsch, Rainer; Boccaccini, Aldo R. (Composites Part B-Engineering, 2014)
In the present study two series of poly(butylene succinate) (PBSu) nanocomposites containing 5 and 20 wt% of silica-nanotubes or strontium hydroxyapatite [Sr(PO)OH] nanorods were prepared by melt mixing at 130 C. From SEM images it was found that SiO nanotubes are well dispersed inside the PBSu matrix while Sr (PO)OH nanorods formed some aggregates. In both cases the mechanical properties of nanocomposites were slightly affected by the amount of nanoadditives. Enzymatic hydrolysis of PBSu and its nanocomposites was studied in aqueous solutions containing a mixture of R. delemar and Pseudomonas Cepacia lipases, at 50 C and pH = 7.2. It was found that all nanocomposites have higher hydrolysis rates than neat PBSu indicating that nanoparticles accelerate the hydrolysis degradation process. The hydrophilicity of nanofillers, the presence of hydroxyl groups and the effect of a ''gap" at the interface due to low adhesion of PBSu matrix and inorganic nanofillers, could increase the enzymatic hydrolysis rate of the polyester matrix. All prepared samples were tested in relevant cell culture using osteoblast-like cells (MG-63) to demonstrate their biocompatibility. It was found that SiO nanotubes support cell attachment, while Sr(PO )OH nanorods decrease cell activity. © 2013 Elsevier Ltd. All rights reserved.
Keywords: A. Discontinuous reinforcement; A. Nano-structures; B. Mechanical properties; B. Microstructures; B. Surface properties